Experimental and Quantum chemical analyses of S-benzyl-β-N-(1-(4-fluorophenyl)ethylidene)dithiocarbazate as biologically active agent. (2022) - Kumar, D.; Srivastava, Anurag; Singh, Kaman; Kumar, Ashok; Bhat, Rayees A.
Highlights: Novel Synthesized Schiff base of dithiocarbazate has been characterized by both Theoretical as well as spectroscopic techniques for better comparison of results. Anti-bacterial activity investigations. VEDA-4 employed for calculating PED% of fundamental vibrations. Theoretical calculations were carried out by using Gaussian 09 (DFT (6–311++ G (d, p)) package. Abstract: S-benzyl-β-N-(1-(4-fluorophenyl)ethylidene)dithiocarbazate (HL), Schiff base of S-benzyl dithiocarbazate was synthesized by 1:1 condensation between S-benzyl dithiocarbazate and 4-Fluoroacetophenone. It's in-vitro cytotoxicity is assayed against two habitually infection causing bacteria strains including gram-positive Staphylococcus aureus and gram-negative Escherichia coli for antibacterial activity. The results showed appreciable biological activity and the activity increased with increase in concentration. The Hard-Soft NS Schiff base (HL) was characterized by FT-IR, H 1 -NMR, Raman, and UV–VIS spectroscopic techniques. Theoretical quantum chemical calculations were performed using DFT in combination with B3LYP exchange correlation functional and 6–311++ G (d, p) basis sets level. The calculated values of chemical potential (µ), HOMO-LUMO energy gap, chemical hardness (ɳ), softness (S), ionization energy (IE), electron affinity (EA), dipole moment (D), electronegativity (χ), electrophilicity (ω) and relative stabilization energy of the compound were 0.30852 eV, 0.15928 eV, −0.1492 eV, 1.5341 eV, −0.22890 eV, −0.07962 eV, 3.4689 Debye, −0.30852 eV, −0.31883 eV and −1624.7264 eV respectively. VEDA-4 (Vibrational energy distribution analysis) software was employed for theoretical FT-IR spectrum analysis which yielded 103 fundamental vibrational modes along with potential energy distribution percentage (PED%) showing non-linearity of HL.